Lessons from comparative primatology for understanding trait covariation and diversity in evolutionary ecology. (7th December 2022) - Correia, Isadora; Gomes, Bruna de França; Villalobos, Fabricio; Ferrari, Stephen F.; Gouveia, Sidney F.
ABSTRACT: Given the position of humans in the tree of life, comparative research on non‐human primates has attracted the interest of researchers in biology, medical sciences, anthropology, psychology, and sociology. Covariation of species' phenotypes has been of particular interest. Learning from the historical development of comparative research with primates should thus be particularly valuable for evolutionary ecology and to improve understanding of phenotypic integration and diversity. Such learning would also help identify knowledge gaps, disputed questions, and new avenues of both basic and applied research in relation to the evolution of primate features and the conservation of our close relatives. We conducted a historical assessment through a non‐systematic review and a systematic review, focusing on how the integration of different research lines in evolutionary ecology focused on primate phenotypic covariation unfolded throughout the 20th Century. The non‐systematic review allowed us to reconstruct the history of the discipline from its earliest origins, when bibliometric assessments were more limited in scope, and to identify the most appropriate keywords for the systematic review. We employed a standard protocol for the systematic review, applying two complementary analyses: co‐occurrence of keywords and bibliographic coupling of references. These analyses described the development of the conceptual and intellectual structures of comparative primatology from 1966 to 2020. By identifying the most influential researchers and concept interrelations, we highlight primate phenotypes critical for the development of the discipline (in particular, brain and body sizes and behavioural patterns), showcasing the reach of these investigations for evolutionary ecology. Overall, our findings emphasise the crucial role that comparative primatology has played in developing the study of phenotypic integration and the very onset of phylogenetic comparative methods. Abstract : Cloud of keywords drawn from the literature on comparative studies on primates, including their morphological, physiological, ecological, and behavioural features, as well as methodological aspects of these studies. The word size is proportional to their appearance in these studies.